THE CONCEPT OF FOIL STRUCTURALLY SENSITIVE INDICATORS OF METAL FATIGUE - Карускевич, М. В. (Science-based technologies, 2013)
The concept of foil structurally sensitive indicators of fatigue is presented. The basis of introduced approach is the deformation relief initiation and development on the metal surface under cyclic loading. It has been considered two types of indicators differing appropriate sensitivity to cyclic loading.